Adaptation practices followed by dairy farmers under adverse climatic conditions in western dry region of India - KANT, KAMALA; SANKHALA, GOPAL; PRASAD, KAMTA; KADIAN, K S (The Indian Journal of Animal Sciences, 2017)
The investigation was conducted in western dry region of India utilizing a descriptive research design. Data were collected through personal interview and focus group discussion. The data were analysed using frequency and percentage. The findings of present study show that majority of the dairy farmers were providing feed twice a day followed by feeding their animals at early morning and late evening, less than recommended floor space in animal house, consult veterinarian + ethno-veterinary practices for managing reproductive problems, using natural service for breeding purpose and growing fodder trees (Khejri, Babul, Ber, Jaal, Ardu and Neem etc.) as a coping strategy to meet the shortage of forage under adverse climatic conditions.